THE POTENTIAL OF TOMATO EXTRACT (Lycopersicum esculentum L.) IN INCREASING THE SERTOLI CELLS AND SPERMATOGENIC CELLS COUNT OF THE CONTRALATERAL TESTICULAR SEMINIFEROUS TUBULES OF RATS (Rattus norvegicus) THAT HAVE TESTICULAR TORSION - Dasrul, Dasrul; Thasmi, Cut Nila; Lubis, Triva Murtina; Awaluddin, Awaluddin; Winaruddin, Winaruddin; Rasmaidar, Rasmaidar; Alifa, Yola (Jurnal Kedokteran Hewan, 2021)
The purpose of this study was to analyze the potential of tomato extract (Lycopersicum esculentum L.) in increasing the Sertoli and spermatogenic cells count of the contralateral testis in white rats (Rattus novergicus) with unilateral torsion. A total of 24 male Wistar white rats, aged 3-4 months old with a weight of 180-200 g were used in this study. The rat samples were randomly divided into 4 treatment groups: Group 1 as a negative control (NC) which consisted of rats without testicular torsion and given tomato extract; Group 2 as a positive control (PC) which consisted of rats with unilateral testicular torsion 720 for 6 hours without given tomato extract; Group 3 as treatment 1 (T1) consisted of rats that were subjected to unilateral testicular torsion 720o for 6 hours and were given tomato extract at a dose of 100 mg/kg BW/day; and Group 4 as treatment 2 (T2) consisted of rats that were subjected to unilateral testicular torsion 720 for 6 hours and were given tomato extract at a dose of 200 mg/kg BW/day. Each group consisted of six rats. Tomato extract was administered orally for 30 days. The observations of the number of Sertoli cells and spermatogenic cells (spermatogonia cells, spermatocytes, and spermatids) were carried out histologically with Hematoxylin-Eosin (HE) staining and the slides were examined with a light microscope. The data obtained was analyzed by ANOVA and continued with Duncan's test. The results showed that the administration of tomato extract significantly increased (P0.05) the number of Sertoli cells and spermatogenic cells of the contralateral testicular seminiferous tubule. Giving tomato extract 100 mg/kg BW/day resulted in an increase in the number of Sertoli cells and better spermatogenic cells than tomato extract 200 mg/kg BW/day. In conclusion the administration of tomato extract after detorsion can increase the number of Sertoli cells and spermatogenic cells of the contralateral testicular seminiferous tubules in white rats subjected to unilateral torsion of 720 for 6 hours